Nurses’ health beliefs about paper face masks in Japan, Australia and China: a qualitative descriptive study - M. Omura (2020)
© 2020 International Council of Nurses Aim: To explore the health beliefs of clinical and academic nurses from Japan, Australia and China regarding wearing paper masks to protect themselves and others, and to identify differences in participants' health beliefs regarding masks. Background: The correct use of face masks and consensus among health professionals across the globe is essential for containing pandemics, and nurses need to act according to policy to protect themselves, educate the public and preserve resources for frontline health workers. Paper masks are worn by health professionals and the general public to avoid the transmission of respiratory infections, such as COVID-19, but there appear to be differences in health beliefs of nurses within and between countries regarding these. Methods: This qualitative descriptive study used content analysis with a framework approach. Findings: There were major differences in nurse participants’ beliefs between and within countries, including how nurses use paper masks and their understanding of their efficacy. In addition, there were cultural differences in the way that nurses use masks in their daily lives and nursing practice contexts. Conclusion: Nurses from different working environments, countries and areas of practice hold a variety of health beliefs about mask wearing at the personal and professional level. Implications for nursing policy and health policy: The COVID-19 pandemic has sparked much discussion about the critical importance of masks for the safety of health professionals, and there has been considerable discussion and disagreement about health policies regarding mask use by the general public. Improper use of masks may have a role in creating mask shortages or transmitting infections. An evidence-based global policy on mask use for respiratory illnesses for health professionals, including nurses, and the general public needs to be adopted and supported by a wide-reaching education campaign.